Dietary intakes and daily distribution patterns of macronutrients in youth soccer players - Martinho, Diogo V.; Naughton, Robert J.; Leão, César; Lemos, João; Field, Adam; Faria, Ana; Rebelo, André; Gouveia, Élvio R.; Sarmento, Hugo (Frontiers in Nutrition, 2023)
Introduction There has been an abundance of dietary analysis research conducted on adult male soccer players, while studies on youth players are lacking. Furthermore, the daily distribution of energy and macronutrient intake throughout the day has been reported to influence training adaptations, but this is often not considered in the literature. This study aims to quantify daily energy and macronutrient intake and assess their distribution over 5 days, and compare daily energy intakes and predicted daily energy expenditure in under-16 male soccer players. Methods The sample included 25 soccer participants aged 14.8–15.7 years. Five-day self-reported food diaries were used to record the food/drink consumption. Intake was analyzed for total daily energy, macronutrient intakes, and distribution among meals (breakfast, lunch, dinner, and snacks). Daily energy expenditure was predicted by resting energy expenditure and physical activity levels developed for youth sports participants. Results The mean total energy intake was 1,928 ± 388 kcal∙day−1, whereas the estimated daily energy expenditure was 3,568 kcal∙day−1. Relative daily protein intakes were lower at breakfast, morning snack, afternoon snack, and night snack compared to lunch and dinner. Discussion Youth soccer players do not appear to meet energy requirements and daily CHO guidelines. Fluctuations in protein intake throughout the day were noted and may influence training adaptations (i.e., muscle protein synthesis and recovery).